Research Progress on the Mechanism of Liquefied Natural Gas Rolling and Preventive Measures - Lin, Fan (International Journal of Natural Resources and Environmental Studies, 2024)
As a core component in the liquefied natural gas (LNG) storage and transportation process, the operational safety and efficiency of LNG storage tanks are crucial to the stability of the natural gas supply chain. This paper delves into the mechanism of LNG rolling and its influencing factors, proposing a series of preventive measures. The findings provide theoretical references and practical guidance for the safety management and risk prevention of LNG storage tanks.